Thermitic thermodynamics : a computational survey and comprehensive interpretation of over 800 combinations of metals, metalloids, and oxides /: a computational survey and comprehensive interpretation of over 800 combinations of metals, metalloids, and oxides. (2020) - Shaw, Anthony Peter Gordon
No abstract available